Educational technologies for prevention and intervention in incidents of falls in hospitalized newborns: a scope review protocol (Research, Society and Development, 2022)
Objective: To map technologies for the prevention and intervention of incidents of falls in hospitalized newborns. Method: Scope review protocol, based on the Joanna Briggs Institute Manual and the Preferred Reporting Items for Systematic Reviews and Meta-analyses Scoping Review checklist. Eligibility criteria were defined as studies that address technologies for prevention and intervention in incidents of falls in hospitalized newborns, published at any time in scientific journals, government websites and/or representative health entities. A detailed search strategy will be used for the Virtual Health Library, PubMed, Scopus and Cinahl databases and/or databases. Titles and abstracts will be screened by two reviewers, who will read the full texts and extract data from the included material, after which a synthesis of the evidence found will be made, to be presented in narrative form, tables, charts and/or images, as a form of to answer the previously defined research question and facilitate the reader's understanding of the research topic.